If Women Are the Best Men in the Philippines, Why Are They Invisible in History? - Fernandez, Albina Peczon (Review of Women's Studies; Vol 6 No 1 (1996): Review of Women's Studies Volume V, Number 2 - Volume VI, Number 1 (1996))
---